Akses keadilan bagi masyarakat marjinal di Indonesia: Reformasi peradilan rakyat kecil melalui program bantuan hukum gratis - Putri, Shella Rizki Dwiyana (Maliki Interdisciplinary Journal, 2026)
This study critically examines disparities in justice access for marginalized communities in Indonesia, including subsistence farmers, daily wage laborers, traditional fishermen, and indigenous groups in remote areas. Structural weaknesses in the formal judicial system—high litigation costs, protracted procedures, and geographical barriers—exacerbate social injustice, violating Article 27(1) of the 1945 Constitution and the fifth pillar of Pancasila. Employing a normative-juridical approach with qualitative analysis of secondary data from Ministry of Law and Human Rights reports, Supreme Court statistics, and case studies by LBH Jakarta and LBH APIK, the research evaluates reforms in small claims courts through free legal aid (pro bono publico) programs managed by Legal Aid Institutes (LBH), Posbakum offices, and local government initiatives in Central Java and NTT. Findings indicate a 40-50% increase in marginalized participation in resolving land disputes, labor wages, and domestic violence cases in remote regions, particularly following Supreme Court Regulation No. 3 of 2017 on prodeo services. Persistent challenges include limited state budget allocation (only 0.5% of APBN for legal aid), inter-agency coordination gaps, low legal awareness among indigenous communities, and e-court digitalization barriers in Papua and Maluku due to poor internet infrastructure. Normative recommendations encompass expanding Posbakum authority in district courts, raising legal aid funding to 2% of APBN, mass training of pro bono lawyers via law faculty partnerships, and integrating restorative mediation based on customary law for efficient small claims resolution. These reforms aim to realize social justice for all Indonesians in line with constitutional mandates.